2012
DOI: 10.2190/om.65.1.c
|View full text |Cite
|
Sign up to set email alerts
|

“A Sound Track of Your Life”: Music in Contemporary Uk Funerals

Abstract: This article considers the role that music plays in contemporary UK funerals and the meaning that the funeral music has for bereaved families. It is based on findings from a recently completed study of 46 funerals funded by the UK Arts and Humanities Research Council. Music contributes to the public ceremony and the personal existential quest of the bereaved. It is important to both the content and process of the contemporary funeral, an event of deep cultural significance in our response as individuals and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 32 publications
1
12
0
1
Order By: Relevance
“…Within each of these themes are located a variety of sub-themes, including those commonly remarked upon such as the use of music (Adamson & Holloway, 2012a;Caswell, 2012), all of which bear detailed consideration in their own right. However, the purpose of this article is to do justice to the comprehensive picture which the study produced through conveying a holistic sense of what these funerals in one north-east corner of England were all about.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within each of these themes are located a variety of sub-themes, including those commonly remarked upon such as the use of music (Adamson & Holloway, 2012a;Caswell, 2012), all of which bear detailed consideration in their own right. However, the purpose of this article is to do justice to the comprehensive picture which the study produced through conveying a holistic sense of what these funerals in one north-east corner of England were all about.…”
Section: Discussionmentioning
confidence: 99%
“…Music was particularly important and not always for the lyrics alone (Adamson & Holloway, 2012a). Broadly speaking, all the choices were made for one of two interrelated reasons -to celebrate and convey the essence of the deceased, and to thereby maintain a connection with them.…”
Section: The Process Of Making Meaningmentioning
confidence: 99%
“…In another study, Adamson and Holloway (2012) examined the role of music in contemporary funerals in the United Kingdom. Based on 29 interviews with funeral professionals countrywide and 46 observations in the north of England, they showed that funeral music contributed to both the creation of a ceremonial event and to the process of meaning-making ( Adamson & Holloway, 2012 , p. 39).…”
Section: Previous Researchmentioning
confidence: 99%
“…Researchers have used various foci but almost all of them zoom in specifically on the event of the funeral. Another meaning of music has been explored in Adamson and Holloway (2012), where it was found to function to break up of spoken words sections during the funereal ceremony. This forms part of Bruin-Mollenhorst's (2018) functional description of the meaning of music.…”
mentioning
confidence: 99%
“…In connection with a ritual passage, for example a confirmation or a wedding, there is a transfer of a person's symbolic and intangible value in the social context (Valkare, 2016). Adamson and Holloway (2012) and Aggedal (2009) have stated their belief that the choice of music at a funeral is the clearest way that families and friends can show who the person was in life. Relatives appear to exert a great deal of influence when it comes to choosing music, and it is important to know how and why this selection also may affect the grieving process by the bereaved.…”
mentioning
confidence: 99%